Blue photo luminescence from 3 mol%Y2O3-doped ZrO2 polycrystals sintered by flash sintering under an alternating current electric field. Issue 5 (May 2020) - Yamashita, Yudai; Kurachi, Tsuyoshi; Tokunaga, Tomoharu; Yoshida, Hidehiro; Yamamoto, Takahisa
Abstract: We investigated the photoluminescence (PL) properties of 3 mol%Y2 O3 -ZrO2 (3YSZ) polycrystals. The 3YSZ polycrystals were prepared by an isothermal flash sintering technique in which an alternating electric field was applied at a predetermined furnace temperature. After flash sintering, clear, visibly blue PL at 2.82 eV (440 nm) was confirmed under an ultraviolet light (3.4 eV (365 nm)); however, no visible PL was observed from 3YSZ polycrystals conventionally sintered using the same raw powders. Thus, the emission of blue PL was induced by the electric field applied during sintering. The obtained PL band was related to excitation at 3.87 eV (320 nm), which is possibly assigned to the singly ionized associated oxygen vacancy defects (AOD + centers). Furthermore, the blue emission was stable after high temperature annealing at 1400 °C for 1 h in air. We possibly attribute the emission of this PL to the stabilization of AOD + centers by the electric field loading during flash sintering.